2008
DOI: 10.1016/j.febslet.2008.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Correlated cleavage of single‐ and double‐stranded substrates by uracil‐DNA glycosylase

Abstract: Uracil-DNA glycosylase (Ung) can quickly locate uracil bases in an excess of undamaged DNA. DNA glycosylases may use diffusion along DNA to facilitate lesion search, resulting in processivity, the ability of glycosylases to excise closely spaced lesions without dissociating from DNA. We propose a new assay for correlated cleavage and analyze the processivity of Ung. Ung conducted correlated cleavage on double-and single-stranded substrates; the correlation declined with increasing salt concentration. Proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 22 publications
(35 reference statements)
2
45
1
Order By: Relevance
“…4B, Table 1). A recent study with UNG using a single short site spacing of 20 bp reported a small transfer efficiency of 0.4 at zero [NaCl], which is similar to the more extensive measurements reported here under different conditions (21). In addition, the strong distance dependence of the intramolecular transfer efficiency of UNG provides an explanation for previous descriptions of UNG as behaving both processively and distributively depending on the site spacing (13,14).…”
Section: Intramolecular Transfer Between Sites Positioned On the Samesupporting
confidence: 73%
“…4B, Table 1). A recent study with UNG using a single short site spacing of 20 bp reported a small transfer efficiency of 0.4 at zero [NaCl], which is similar to the more extensive measurements reported here under different conditions (21). In addition, the strong distance dependence of the intramolecular transfer efficiency of UNG provides an explanation for previous descriptions of UNG as behaving both processively and distributively depending on the site spacing (13,14).…”
Section: Intramolecular Transfer Between Sites Positioned On the Samesupporting
confidence: 73%
“…Similar to what was observed for T4 endonuclease V, the processivity of Udg appears to be highly dependent on salt conditions for both substrates. However, Udg also appears to switch between a distributive and processive mechanism depending on the identity of the linear substrate [2124, 26]. As evidence for a combination of sliding and distributive search modes grew, linear substrates were designed with precisely-spaced damage sites to allow for a determination of how far the glycosylase slides before dissociating from the DNA strand.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the EcoRI enzyme bound to the site between the lesions decreased the processivity of AAG by only 50%, indicating that some of the glycosylases were able to hop over the restriction enzyme to process the second lesion. In other studies, Udg was shown to be able to bypass both nicks and single-stranded gaps, albeit with reduced rates of correlated cleavage of uracils on the opposite side of the gap [25, 26]. In order to detect intersegmental transfer, Hedglin et al designed substrates consisting of two damaged oligos connected by a flexible PEG tether, increasing the local concentration of the two oligos while preventing sliding between them.…”
Section: Introductionmentioning
confidence: 99%
“…Sliding along the DNA backbone without release is often referred to as “facilitated diffusion,” but glycosylases may also make small “hops” between close sites on the DNA or traverse longer distances through intrastrand and/ or interstrand transfer events (for reviews see [5658]). Ensemble methods measuring correlated cleavage of closely spaced damage sites in long oligodeoxyribonucleotides provided evidence that the glycosylases were capable of remaining in continuous contact with the DNA molecule after removing a lesion [5966]. However, direct visualization of the movement of glycosylases along longer tracts of undamaged DNA remained a challenge until a breakthrough occurred using single molecule (SM) fluorescence microscopy imaging.…”
Section: How Do the Dna Glycosylases Search For Oxidatively Damagementioning
confidence: 99%